Designing a Forex Trading and Equity Investment Strategy for the New-State Capital Hedge Fund - Malik, Rizvan (2008)
Construct the investment strategy for the New-State Capital Hedge Fund. Identify profit making opportunities in Foreign Exchange (Forex) & Equities using both conventional and non-conventional indicators. The author is to articulate and document his current knowledge in the chosen area in order to stimuate ideas in creating potential investment strategies. Justify knowledge with actual results in a genuine live investment. Critique and evluate the effectiveness of the proposed investment strategy. Conclude with lessons learned and future research.